Human resource management practices of Japanese companies in India: dealing with the transfer-adaptation dichotomy. Issue 3 (7th August 2017) - Maharjan, Mohan Pyari; Sekiguchi, Tomoki
Abstract : Purpose: Based on the international human resource management perspective, this paper aims to explore and explain the human resource (HR) practices of Japanese multinational companies (MNCs) operating in India. Design/methodology/approach: This paper applies a qualitative methodology. The study is based on 17 semi-structured interviews that were conducted within the subsidiaries of 10 Japanese MNCs in India. Findings: The respective HR practices are differently influenced by cultural and institutional factors. Cultural similarity, unique social context and the evolving labor market shape the HR practices of Japanese MNCs in the Indian context. Research limitations/implications: The generalizability of findings might be limited because of the nature of methodology. Future research could collect additional qualitative data and conduct quantitative studies to test the findings of this research. Practical implications: A unique combination of HR practices could be formed by addressing the changes in the local institutional environment and retaining the core philosophy of the parent company. Originality/value: This research adds value to the transfer-adaptation dichotomy by presenting how institutional and cultural factors differently influence the transfer of respective HR practices.